Perceptions of individual and societal onset of old age: associations with views on aging in a sample aged 16 to 96 years. - Wettstein, Markus; Kornadt, Anna E.; Warner, Lisa Marie; Kessler, Eva-Marie (European Journal of Ageing, 2025)
There are considerable interindividual differences regarding when individuals perceive someone as "old" (i.e., perceived individual onset of old age). Individuals might also differ in when they believe that society considers someone as "old" (i.e., perceived societal onset of old age). We investigated how multiple indicators of views on aging (age stereotypes, subjective age, age knowledge, perceived ageism), socio-demographic factors (age, sex, education, region of residence), and self-rated health are related to perceptions of individual vs. societal onset of old age and with the difference between both measures in an age-heterogeneous sample. In the Age_ISM Germany survey, a representative sample of 2,000 Germans was recruited (age range 16–96 years, M = 56.6 years). We ran structural equation models with sampling weights and found that individuals report a perceived individual onset of old age that was on average more than eight years later than their perceived societal onset of old age. Perceived ageism was associated with an earlier perceived individual and societal onset of old age as well as with a greater discrepancy between both indicators. Feeling younger was associated with a later perceived individual onset of old age. Associations of views on aging, socio-demographics, and self-rated health with perceived individual onset of old age did not vary across age groups, whereas age-group differences emerged for perceived societal onset of old age. Our findings advance theoretical frameworks on views on aging by demonstrating a meaningful discrepancy between perceived individual and societal onset of old age, which are uniquely associated with views on aging.